The Relevance of Bong Joon-ho’s Parasite Movie to the Holy Book of the Islamic Religion - Setiyono, Junaedi (International Proceedings of Nusantara Raya, 2023)
Research on the relevance of the first South Korean film winning the 92th Academy Award with Islamic teachings found in the Koran is important to conduct because of the popularity of South Korean films in Indonesia. The phenomenon that South Korean films have become the favourite films of young people has been acknowledged. Due to the popularity of Korean films among young Indonesians, the researcher would like to describe the relevance of Bong Joon-ho’s movie Parasite to Islamic teachings found in the Koran. Because most of Indonesia's population (86.7%) are Islam followers, the findings will be of necessity. The method used is the Mixed Method (Hesse-Biber, 2010) involving a triangulation approach (Oliver-Hayo and Allen, 2006). The data is mainly obtained from the available English subtitles belonging to the film. Based on the analysis and interpretation of the data, the researcher describes the relevance of the movie to the verses in the Koran. Kim Ki-taek, one of the main characters, believes that life is merely to undergo, no need to plan. This is in accordance with the verses in the Koran that support the concept of Jabariyah (at least 2 verses). Kim Ki-woo, another main character, believes the opposite, namely that life needs to be planned. And this is in accordance with the concept of Qadariyah which is contained in the verses of the Koran (at least in 3 verses). There are couples or binary opposition between rich and poor, innocent and sly, etc. that can easily be found. This is in accordance with the verses of the Koran about creatures that were created in pairs (at least 3 verses). In the film there is a scholar's rock, which becomes something special. In the Koran, the special wooden staff or rod belonging to the Prophet Moses can be found (at least 3 verses). And as a whole the movie metaphorically depicts the world and its contents which are just mere games and jokes that can be found in the verses of the Koran (at least 2 verses).